Constituting Old Age in Early Modern English Literature, from Queen Elizabeth to King Lear - Martin, Christopher, 1957- (Book collections on Project MUSE., 2012)
How did Shakespeare and his contemporaries, whose works mark the last quarter century of Elizabeth I's reign as one of the richest moments in all of English literature, regard and represent old age? Was late life seen primarily as a time of withdrawal and preparation for death, as scholars and historians have traditionally maintained? In this book, the author examines how, contrary to received impressions, writers and thinkers of the era - working in the shadow of the kinetic, long-lived queen herself - contested such prejudicial and dismissive social attitudes. In late Tudor England, the author argues, competing definitions of and regard for old age established a deeply conflicted frontier between external, socially "constituted" beliefs and a developing sense of an individual's "constitution" or physical makeup, a usage that entered the language in the mid-1500s. This space was further complicated by internal divisions within the opposing camps. On one side, reverence for the elder's authority, rooted in religious and social convention, was persistently challenged by the discontents of an ambitious younger underclass. Simultaneously, the aging subject grounded an enduring social presence and dignity on a bodily integrity that time inevitably threatened. In a historical setting that saw both the extended reign of an aging monarch and a resulting climate of acute generational strife, this network of competition and accommodation uniquely shaped late Elizabethan literary imagination. Through fresh readings of signature works, genres, and figures, the author redirects critical attention to this neglected aspect of early modern studies.